2021
DOI: 10.3390/su13126660
|View full text |Cite
|
Sign up to set email alerts
|

Oil Pollution Affects the Central Metabolism of Keystone Vachellia (Acacia) Trees

Abstract: Vachellia (formerly Acacia) trees are native to arid environments in Africa and the Arabian Peninsula, where they often support the local animal and plant communities acting as keystone species. The aim of this study was to examine whether oil pollution affected the central metabolism of the native keystone trees Vachellia tortilis (Forssk.) and V. raddiana (Savi), as either adults or seedlings. The study was conducted in the Evrona Nature Reserve, a desert ecosystem in southern Israel where two major oil spil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…We find it more likely that higher water availability to the polluted trees due to their central location in the streambed, rather than direct effects of the oil pollution, accounted for this pattern. Although our hypothesis that oil pollution would reduce the activity both invertebrate and vertebrate predators was not confirmed, oil pollution is a major threat to this ecosystem: It was shown to change the soil microbial community (Girsowicz et al, 2018) and parasitoid abundance (Möller et al, 2020), as well as to reduce Vachellia seed germination (Tran et al, 2018), seedling recruitment (Nothers et al, 2017), and to modify the tree metabolism (Ferrante et al, 2021).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We find it more likely that higher water availability to the polluted trees due to their central location in the streambed, rather than direct effects of the oil pollution, accounted for this pattern. Although our hypothesis that oil pollution would reduce the activity both invertebrate and vertebrate predators was not confirmed, oil pollution is a major threat to this ecosystem: It was shown to change the soil microbial community (Girsowicz et al, 2018) and parasitoid abundance (Möller et al, 2020), as well as to reduce Vachellia seed germination (Tran et al, 2018), seedling recruitment (Nothers et al, 2017), and to modify the tree metabolism (Ferrante et al, 2021).…”
Section: Discussionmentioning
confidence: 77%
“…In this area, two large oil spills occurred in 1975 and 2014, during which around 10,000 m 3 and 5,000 m 3 of crude oil, respectively, leaked into the area jeopardizing the entire ecosystem (Golan et al, 2016). Oil pollution has been shown to affect the metabolism, recruitment, and germination of keystone tree species in this area (Ferrante et al, 2021;Golan et al, 2016;Nothers et al, 2017) and may negatively affect insect biodiversity (Möller et al, 2020) with potential cascading effects on biotic interactions. We focused our study on predation, a fundamental ecosystem function (Hairston et al, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…Another highly emergent research area in the cluster was found to be health risk assessment caused due to a variety of factors arising from oil spills like seafood contamination 97 , cancer caused due to polycyclic aromatic hydrocarbons 102 and health risk caused by exposure to benzene 31 . Cluster 2 is highlighted in green color in Figure 4 and is anchored with keywords like bioremediation 7,95,14,90 biodegradation 7,43,39 , metabolism 25,110,36 and microbial community 47,112,94 . As highlighted in cluster 2 of the cocitation analysis shown in Figure 1 this cluster also highlights the use of bioremediation and biodegradation for reducing the impact of oil spills on the environment 7,43 .…”
Section: Co-occurrence Analysismentioning
confidence: 99%
“…As highlighted in cluster 2 of the cocitation analysis shown in Figure 1 this cluster also highlights the use of bioremediation and biodegradation for reducing the impact of oil spills on the environment 7,43 . Another interesting theme highlighted in the cluster corresponds to changes in metabolic scope indicating changes in fishes' ability to face environmental contingencies 25,110,36 and microbial community dynamics that lead to oil degradation 47,112 . Cluster 3 is shown with blue color in Figure 4 and corresponds to marine toxicity and its impact on aquatic life.…”
Section: Co-occurrence Analysismentioning
confidence: 99%
“…Acacia trees (several species of the genus Vachellia (Wight & Arn. )), the keystone species in this ecosystem, were found to be affected by oil spills [16,17]; germination, seedling height, leaf number, stem diameter, and root growth were significantly reduced in oil-contaminated soils than in clean soils [17]. Moreover, five different metabolites (alanine, β-alanine, acid, maltose, and phosphoric acid) had significantly different levels in the oil-contaminated and clean soils of Acacia trees [16].…”
Section: Introductionmentioning
confidence: 98%